Individual and healthcare system factors influencing antenatal care attendance in Saudi Arabia - W. Alanazy; A. Brown (BMC, 2020)
Abstract Background The World Health Organisation recommends women have at least four antenatal care visits (ANC) during a low risk pregnancy. However, in Saudi Arabia, many mothers miss these appointments, placing their health and that of their baby at risk. Limited research which has explored why this is happening has focused on low maternal education or personal barriers such as lack of transport. The aim of the current research was therefore to understand what factors at the individual and healthcare systems level were associated with missing antenatal care in Saudi Arabia. Methods Two hundred and forty-two pregnant women in their third trimester completed a questionnaire examining their care attendance (appointments missed, planned future attendance, timing of first appointment) alongside barriers to attending care. These included maternal demographic background, health literacy, personal barriers, health care system factors and staff communication). Results Over half of women surveyed had missed at least one appointment and a third had delayed their care. Mothers who had missed or delayed appointments blamed health care system factors such as poor clinic facilities and waiting times. Attending care was not associated with maternal education or literacy, although mothers with a lower level of literacy were more likely to delay care. However, perceptions of staff communication, consistency and care were lower amongst mothers who had missed at least one appointment. Conclusions Although in previous research health professionals believe it is maternal education that leads to poor attendance, in our sample at least, perceptions of staff communication and clinic facilities were instead associated with attendance. Making changes at the health care level e.g. through adapting clinic times and investing in staff training may increase antenatal care attendance in Saudi Arabia.